PARIPATETIC TRADITION AND METAPHYSICS IN AL-FARABI’S PHILOSOPHY: THE WAY OF HAPINESS - Aulia Rachman (UIN Sunan Kalijaga Yogyakarta, 2020)
AbstractThis article discusses about metaphysics in al Farabi's peripatetic philosophy, particularly about happiness. In the historical study of philosophy, this belief was grounded through the peripatetic method. In this peripatetic tradition, there are several central themes that become profound discourses in philosophical discourse, including metaphysical concepts. The metaphysical concept has a unique distinction in its position in Islamic philosophy. One of them is from Al-Farabi's view, which views that mastery of metaphysical concepts has an important role in creating happiness. For this reason, this paper will discuss what is the peripatetic tradition in history, metaphysical concepts that exist in the realms of Islamic philosophy and discuss the relationship between metaphysical concepts and the concept of happiness owned by Islamic philosophers, namely Abu Nasir Muhammad bin al-Farakh Al-Farabi (872-951).